Virtual Play and the Victorian Novel The Ethics and Aesthetics of Fictional Experience - Gao, Timothy (Humanities, 2021)
Virtual Play and the Victorian Novel proposes a literary history of virtual reality, stemming from imaginary worlds created by nineteenth-century novelists such as Charlotte Bronte, Charles Dickens, and William Thackeray, providing innovative approaches to interpreting realist fiction and fictional realities for scholars and students of literature. This title is also available as Open Access on Cambridge Core.